Tenogenically Induced Allogeneic Peripheral Blood Mesenchymal Stem Cells in Allogeneic Platelet-Rich Plasma: 2-Year Follow-up after Tendon or Ligament Treatment in Horses - Beerts, Charlotte; Suls, Marc; Broeckx, Sarah Y.; Seys, Bert; Vandenberghe, Aurélie; Declercq, Jeroen; Duchateau, Luc; Vidal, Martin A.; Spaas, Jan H. (Frontiers in Veterinary Science, 2017)
Poor healing of tendon and ligament lesions often results in early retirement of sport horses. Regenerative therapies are therefore being explored as alternative treatment for these injuries. In this study, an intralesional injection was performed with allogeneic tenogenically induced MSCs and PRP 5 to 6 days after diagnosis of SL (n=68) or SDFT (n=36) lesion. Clinical, lameness and ultrasonographic evaluation was performed at 6 and 12 weeks. Moreover, a survey was performed 12 and 24 months after treatment to determine how many horses were competing at original level and how many re-injured. At 6 weeks 88.2% of SL (n=68) and 98.2% of SDFT lesions (n=36) demonstrated moderate ultrasonographic improvement. At 12 weeks, 93.1% of SL (n=29) and 95.5% of SDFT lesions (n=22) improved convincingly. Moreover, lameness was abolished in 78.6% of SL and 85.7% of SDFT horses at 12 weeks. After 12 months (n=92) 11.8% of SL and 12.5% of SDFT horses re-injured, whereas 83.8% and 79.2% returned to previous level, respectively. At 24 months (n=89) after treatment, 82.4% (SL) and 85.7% (SDFT) of the horses returned to previous level. A meta-analysis was performed on relevant published evidence evaluating re-injury 24 months after stem cell based versus conventional therapies. Cell therapies resulted in significantly lower re-injury rate two years after treatment based on literature data (P<0.0001).